2013
DOI: 10.4161/biom.24651
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the viscoelastic behavior of collagen matrices through relaxation time distribution spectrum

Abstract: This study aims to provide understanding of the macroscopic viscoelastic behavior of collagen matrices through studying the relaxation time distribution spectrum obtained from stress relaxation tests. Hydrated collagen gel and dehydrated collagen thin film was exploited as two different hydration levels of collagen matrices. Genipin solution was used to induce crosslinking in collagen matrices. Biaxial stress relaxation tests were performed to characterize the viscoelastic behavior of collagen matrices. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 57 publications
6
39
0
Order By: Relevance
“…Our tension results indicate good agreement with previous studies that demonstrated a significant decrease in mechanical properties Representative DSC thermograms of MD (a) and DM (b) in either the dry or rehydrated state of collagen matrices going from the dry to the wet state [18,19]. The present study did not determine the specific mechanism for the change in mechanical properties following rehydration of the different collagen matrices.…”
Section: Discussionsupporting
confidence: 93%
“…Our tension results indicate good agreement with previous studies that demonstrated a significant decrease in mechanical properties Representative DSC thermograms of MD (a) and DM (b) in either the dry or rehydrated state of collagen matrices going from the dry to the wet state [18,19]. The present study did not determine the specific mechanism for the change in mechanical properties following rehydration of the different collagen matrices.…”
Section: Discussionsupporting
confidence: 93%
“…The greatest degrees of collagen fiber realignment and cell reorientation that occurred at the slow loading rate (Figs. 4 and 5) may be due to the viscoelastic properties of the neurons and their surrounding collagen matrix [75][76][77]. Viscoelasticity may limit fiber rotation and stretch during rapid NCC stretch because hydrogen bonds between and within the collagen molecules are less likely to break under rapid loading [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Since the nonlinear properties of collagen and neurons can induce higher stress and less stress relaxation in tissue undergoing more rapid stretch [5,77,80], neurons stretched at the fast rate were hypothesized to experience greater loads and to exhibit elevated activity compared to those undergoing slower loading. However, no difference in pERK production was observed between the two rates, regardless of the distraction magnitude (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The solutions were kept overnight with continuous stirring at 4º C before performing the measurements with and without CCSNP for cross-linking [47].…”
Section: Viscositymentioning
confidence: 99%